Mechanical Properties of Thin-Film Parylene–Metal–Parylene Devices - Lee, Curtis D.; Meng, Ellis (Frontiers in Mechanical Engineering, 2015)
Structures and testing methods for measuring the adhesion strength, minimum bending diameter, and bending fatigue performance of thin film polymer electronic architectures were developed and applied to Parylene-metal-Parylene systems with and without the moisture barrier Al2O3 (deposited using atomic layer deposition (ALD)). Parylene-metal-Parylene interfaces had the strongest average peel test strength and Parylene-Parylene interfaces had the weakest peel. Layers of ALD Al2O3 deposited within the device increased the average peel strength for Parylene-Parylene interfaces when combined with silane A-174, but did not increase the Parylene-metal-Parylene interface. Metal traces in the middle of 24 µm thick Parylene-metal-Parylene devices had a minimum bending diameter of 130 µm before breaking and being measured as an open circuit. The addition of one layer of Al2O3 above the traces allowed them to be completely creased when bent away from the Al2O3 layer without producing an open circuit, but increased the minimum bending diameter to 450 µm when bent away from the Al2O3. Although fatigue testing produced cracks in all devcies after 100k bends, the insulation of the Parylene-metal-Parylene devices without Al2O3 performed well with electrochemical impedance spectroscopy (EIS) showing only small decreases in impedance magnitude and small increases of impedance phase at low frequencies. However, devices with Al2O3 failed during EIS due to Al2O3 being deteriorated by water.